Lost for words : loss and bereavement awareness training - Holland, John, 1948- (JKP resource materials., 2005)
Lost for Words is an innovative 'loss awareness' training package designed for teach-ers and carers supporting children who are experiencing bereavement, be it through death or any other kind of loss. Developed from collaborative multi-agency and multi-professional work with psychologists, educationalists, social workers and nurses, this package is designed for use by trainers over the course of a day, or over several days. It offers trainers and course delegates crucial guidance, soundly underpinned by research carried out with bereaved children and their parents, in schools, and by the 'Iceb.